INTERNALISASI NILAI-NILAI PENDIDIKAN AKHLAK MELALUI PENGAJIAN KITAB BIDAYATUL HIDAYAH DI KELAS VIII PUTRI MTS UNGGULAN NURIS JEMBER - Achmad Faisol; Malinda Azizah; Luluk Mashluchah (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
Advances in technology and science in this era of globalization have made the worldsituation transparent, the barriers between national cultures have begun to disappear,resulting in the ease of foreign cultures influencing other cultures. To protect againstnegative things, serious treatment is needed in the form of moral development throughreligious education. The aim of this research is to analyze the internalization transformationstage, the transaction stage and the trans-internalization stage of the value of moraleducation through the recitation of the Bidayatul Hidayah book for Class VIII Girls at MTsUnggulan Nuris Jember. The research method used is qualitative with a phenomenologicalapproach. The research results show that several processes used in transforming the valuesof Islamic religious education are lectures (mau'idzah), stories and taking ibroh, as well asthe sorogan method. This process is used to transform the values of aqidah, shari'ah andmorals. Where at this stage it is taught how to transform knowledge to students. So thatstudents really know and understand what is taught by the teacher and what is taught bythe students themselves or through discussion. At the transaction stage, the values of moraleducation are shown in steps in the form of habituation and punishment. This habit isapplied in internalizing the values of Islamic education both in faith, shari'ah and morals.Next, in the value transinternalization stage, the most influential thing is example. This isshown in the example set directly by caregivers and teachers. This example consists of how to worship Allah SWT, how to carry out the commandments of the Shari'ah and how tobehave well towards others. The conclusion of this research is that the internalization ofmoral education values through the recitation of the Bidayatul Hidayah Book is shown inseveral processes, including the transformation of Islamic education values in the form oflectures, stories and sorogan, value transactions in the form of habituation and punishment,and the trans internalization of values shown by morals that are exemplified directly bycaregivers and teachers.